Antecedents and Consequences of Materialism: An Integrated Theoretical Framework - Duh, Helen I. (Journal of Economics and Behavioral Studies, 2015)
Materialism has become an integral part of consumers’ economic activities and modern day living, with mainly negative consequences reported from materialists’ lifestyle. Some of the reported negative consequences of materialism are increasing consumer debt and bankruptcy, shrinking saving, economic crisis and lower levels of life satisfaction and well-being. Consequently, economic psychologists, consumer researchers, sociologists and family psychologists are studying the antecedents of materialism, but there is yet to be an agreement as to how the construct should be defined and on what causes or predicts materialism. Critics of materialism have often seen only negative consequences and blamed marketing activities for the growth of materialism, but substantial academic literature and empirical studies report biological, social, cultural, socio-economic, psychological and even political factors driving materialism. There is therefore a need to develop an integrated and comprehensive theoretical framework, which delineates the various predictors of materialism. There is also the need to highlight the negative, as well as positive consequences of materialism for the interest of retailers, consumer interest groups and policy makers.